Magnets Branding Become a Solution for Halal Tourism in Alamendah Tourism Village - Maulida, Nazira; Imam Indratno (CV. Media Digital Publikasi Indonesia, 2024)
Brand Identity is important for halal tourism. Because with Brand Identity, the branding that is created will be more attached to the minds of tourists. Because with brand identity, the branding that is created will have distinctive characteristics and the branding that is created will be more detailed, not only limited to a logo. In this study, an analysis will be carried out using the magnet branding method consisting of 15 steps with the Stratified Random Sampling data collection method. This study is different from other studies that discuss branding for tourism in general, this study discusses branding for halal tourism in tourist villages. The result is that this magnet branding is indeed needed for halal tourism in Alamendah Tourism Village so that tourism in Alamendah Tourism Village has advantages compared to the surrounding tourist villages through its halal tourism. For the planning of halal tourism development, namely halal educational park and path for disabled.